ISOLATION AND IDENTIFICATION OF PLANT PARASITIC NEMATODES AFFECTING TOMATO (SOLANUM LYCOPERSICUM, LINN.) IN GIWA LOCAL GOVERNMENT AREA, KADUNA, NIGERIA - Isa, Ibrahim; Eze, Marvise Chinyere; Bayo, Kamba (FUDMA JOURNAL OF SCIENCES, 2024)
Plant-parasitic nematodes are the major biotic stressor in crop cultivation. They are recognized as one of the greatest threats to crops worldwide. The study evaluated nematodes that affect tomato in Giwa Local Government area, Kaduna State, Nigeria. Samples were collected from two selected farms each from seven locations. The tomato samples were classified as diseased and healthy based on the appearance of the plants. In each farm, four samples were taken during the growing season; two from diseased plants and two from apparently healthy looking plants. Similarly, soil samples from diseased and apparently healthy soil were collected. The soil and tomato samples were extracted using Cobb-Sieving and Decanting method. Descriptive statistics, students t-test and species diversity were used to analyze the data. Nineteen (19) genera of plant parasitic nematodes were isolated and identified, with 18 genera each in diseased soil and root samples, 12 and 9 genera from apparently healthy soil and roots respectively. Scutellonema spp. (1121) had the highest number of nematodes genera while Tetylenchus (20) had the lowest, in diseased soil samples. In diseased root samples, Meloidogyne (415) had the highest nematodes while Tetylenchus (10) had the lowest number of nematodes. In apparently healthy soil samples, Scutellonema (522) had the highest number of collection, while Tylenchorynchus (20) had the least. In apparently healthy root samples, Pratylenchus (415) had the highest and Hoplolaimus (10) had the lowest number of collection across all the locations. There was no significant difference (p > 0.05) in the presence of nematodes in the...